Data for: Dielectric Breakdown Strength of Unidirectional Fiber Composites: Weibull Analysis of Fiber Orientation and Size Effects - Arvidsson, Karl; Ranathunga Arachchige, Ishara A.U.; Fernberg, Patrik (Luleå University of Technology, 2026)
The dataset contains experimental data from dielectric strength testing of unidirectional glass fiber–epoxy composites. The composite laminates were manufactured by pressing prepregs and exhibited low porosity. Testing was performed in a Phenix 6CC100-5/D149 under alternating voltage according to ASTM D149-20. Electrodes and specimen were submerged in transformer oil to prevent surface flashover. Flat, parallel electrodes covering the entire specimens were used to apply a continuously increasing potential difference, corresponding to an electric field increase of 0.25 (kV/mm)/s. Samples with varying fiber angles relative to the applied electric field (0°, 30°, 45°, 60°, 90°), electrode gaps (2 mm, 4 mm, 8 mm, 16 mm), and cross-sectional areas (30 mm², 50 mm², 70 mm²) were tested. Specimens for which a clearly carbonized breakdown path in the material could not be visually identified after the first test were subjected to a second test.

Datasetet innehåller experimentell data från dielektrisk hållfasthetsprovning av enkelriktade glassfiber-epoxy kompositer. Kompositlaminaten har tillverkats genom pressning av prepregs och uppvisat låg porhalt. Provningen har utförts i en Phenix 6CC100-5/D149 under växelspänning enligt standard ASTM D149-20. Elektroder och provkropp var nedsänkta i transformatorolja för att förhindra överslag utanför provkroppen. Plana, parallella elektroder, täckande hela provkropparna, har använts för att lägga på en konstant ökande potentialskillnad, motsvarande en ökning av det elektriska fältet med 0.25 (kV/mm)/s. Provkroppar med varierande fibervinkel i förhållande till pålagt elektriskt fält (0°, 30°, 45°, 60°, 90°), elektrodavstånd (2 mm, 4 mm, 8 mm, 16 mm) och tvärsnittsarea (30 mm^2, 50 mm^2, 70 mm^2) har testats. Provkroppar där ett tydligt förkolnat genomslag i materialet inte kunde urskiljas visuellt efter första testet har testats en andra gång.
Data för: Dielektrisk hållfasthet av enkelriktade fiberkompositer: Weibull-analys av fiberorientering och storlekseffekter
Keywords: composites; kompositer; electric properties; elektriska egenskaper; electrical breakdown; glass fiber reinforced plastics; Dielectric strength; Dielektrisk hållfasthet; Composite Science and Engineering; Kompositmaterial och kompositteknik; Power Systems and Components; Elkraftsystem och -komponenter